Influence of the regularization scheme in the QCD phase diagram in the PNJL model - Saucedo Rincón, Jonathan; Paz, Antonio; Flores Baez, Francisco Vicente; Ibarra Morones, José Rubén (De Gruyter Open, 2023)
In the context of the SU(2) quark flavor version of the Nambu–Jona-Lasinio model extended by the Polyakov loop, the effect of the regularization scheme on the quantum chromodynamics phase structure at finite volume was studied. The way in which the phase diagram changes with the type of Polyakov loop potential considered in this study was also investigated. In this study, a polynomial and a logarithmic potential were used. On the other hand, a regularization scheme that satisfies the thermodynamics properties such as the Stefan–Boltzmann limit was chosen.